THE INTERACTION IN A FORUM OF DISCUSSION, BASED ON THE PARTICIPATION OF STUDENTS AND ADVISER. - Alfaro., Marco Antonio Pereida; Ponce, Daniel Montes (IJRDO- Journal of Educational Research, 2017)
It addresses the work within the discussion forums to identify how is the participation of students in their learning, within the subject Project I of the Licentiate in Technologies and Information (LTEI) of the Virtual University System of the University of Guadalajara ( UDGVirtual), during the 2016 A cycle. A content analysis of the types of interaction in the messages of the forums is done, according to the classification of Hirumi (2002). The course in which the research was conducted is nested in a Virtual Learning Environment (AVA) Moodle. A solid open source-learning platform responds to the requirements of its academic model. This exploration was the type of strategies used in the management of interactions within the dynamics of the Project I of the Licentiate in Technologies and Information (LTEI) of the System of Virtual University of the University of Guadalajara (UDGVirtual). It was possible to conclude that the advisors and the majority of the students participated in the forums of irregular form, since some published more messages than others did and the participations varied in each forum. Likewise, the most frequent type of interaction in the course of Project I was that of TeacherStudent. The lowest frequency was located in the Teacher-Group type.